Chemical composition, thermal stability and antioxidant properties of tea seed oils obtained by different extraction methods: Supercritical fluid extraction yields the best oil quality - Shao, P.; Liu, Q.; Fang, Zhongxiang; Sun, P. (Wiley-VCH Verlag, 2015)
A comparison study has been performed for tea seed oils (TSO) extracted from different methods and sources, which were oil from cold-pressing of tea seeds [TSO(CP)], oil from supercritical fluid extraction of seeds [TSO(SCF)], and oil from supercritical fluid extraction of tea seed cake [TSCO(SCF)]. The chemical composition, thermal stability, antioxidant properties, and physicochemical properties of the oils were determined. The main ingredient in seed and cake was fat, fiber, total sugar, and considerable amounts of amino, 74.59 and 93.25g/100g protein, respectively were found. The results also indicated that oleic acid and linoleic acid were the dominant unsaturated fatty acids in tea seed oils, irrespective of extraction methods and sources. The TSO(SCF) contained the highest levels of squalene, lupeol, and total sterols whereas TSCO(SCF) and TSO(CP) had higher contents of total phenolics and a-tocopherol. The TG/DTG curves showed TSO(CP) and TSO(SCF) were more thermally stable than TSCO(SCF), and the antioxidant activity assays demonstrated that TSO(CP) and TSCO(SCF) exhibited stronger radical scavenging ability. The overall physicochemical properties of the tested oils indicated that TSO(SCF) had the best oil quality. This work may be useful to food oil industry to produce high quality tea seed oils through utilization of suitable oil extraction methods and raw materials. Practical applications: The growing consumption of green tea promoted the increased production of tea seed, which has totaled as much as 1.6 million tons annually since 2011. As an important source of edible oil, the exploitation rate of tea seed is insufficient (=1%) in China. This study indicates that oil extracted from tea seed as well as cold-pressing cake can be exploited for high quality edible oil because of similar fatty acid composition and better bioactive compound composition (e.g., a-tocopherol, total phytoterols, and lupeol) compared to olive oil. Further, the evaluation of thermal stability provides basis for oil's refining to prepare salad oil, mayonnaise, etc. TSO(SCF) and TSCO(SCF) both had good antioxidant activity, which is applicable in the industry of skincare.Practical applications: The growing consumption of green tea promoted the increased production of tea seed, which has totaled as much as 1.6 million tons annually since 2011. As an important source of edible oil, the exploitation rate of tea seed is insufficient (≤1%) in China. This study indicates that oil extracted from tea seed as well as cold-pressing cake can be exploited for high quality edible oil because of similar fatty acid composition and better bioactive compound composition (e.g., α-tocopherol, total phytoterols, and lupeol) compared to olive oil. Further, the evaluation of thermal stability provides basis for oil's refining to prepare salad oil, mayonnaise, etc. TSO(SCF) and TSCO(SCF) both had good antioxidant activity, which is applicable in the industry of skincare. {graphic removed}. A comparison study has been performed for tea seed oils (TSO) extracted from different methods and sources, which were oil from cold-pressing of tea seeds [TSO(CP)], oil from supercritical fluid extraction of seeds [TSO(SCF)], and oil from supercritical fluid extraction of tea seed cake [TSCO(SCF)]. The chemical composition, thermal stability, antioxidant properties, and physicochemical properties of the oils were determined.